Copying, adaptation and invention in the Tempietto of the Volto Santo in Lucca - Davies, Paul (Aesthetica Preprint, 2024)
This essay considers the role of copying in the architectural oeuvre of the Lucchese sculptor-architect Matteo Civitali (1436-1501), analysing his singular approach to the appropriation of elements from his chosen models. In doing so, it considers first the shrine of San Regolo and the tomb of Pietro Noceto in Lucca Cathedral, arguing that Civitali relied heavily on single – usually celebrated – works in designing his projects, often taking both composition and individual details from the same source, while at the same time managing to inject them with a degree of invention, so that high degrees of copying and invention can be found in the same design. It goes on to contend that he used the same procedure in the Tempietto del Volto Santo, a small octagonal structure also housed in the cathedral, identifying the source for its composition and detailing as being a portal in the Casa Porcari in Rome, which is partly antique and partly fifteenth-century in date. In discussing these works, the essay reflects on the problems involved in discussing copying in the context of classical architecture.